2021
DOI: 10.1002/gps.5491
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism, negative life events, and dementia in older White and Black Brazilians

Abstract: Objective Exposure to negative life events (NLEs) and neuroticism are associated with dementia. It is unknown whether neuroticism explains or modifies the association of NLEs with dementia in older Black and White Brazilians. Methods A total of 1747 decedents 65 years and older White and Black (11% Black and 23% Mixed) Brazilians, 53% women, were included in the analyses. Data were obtained in a face‐to‐face interview with an informant (71% their children) who knew the decedents for 47 years on average. Dement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…We used the informant portion of the Clinical Dementia Rating Scale 13 to classify dementia and MCI proximate to death, as described previously. 14 Function in each of six domains (memory, orientation, judgment and problem solving, community affairs, home and hobbies, personal care) was rated on a 5‐point scale. An algorithm converted the six domain scores to an overall rating of no cognitive impairment (score = 0), MCI (score = 0.5), or dementia (score >0.5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the informant portion of the Clinical Dementia Rating Scale 13 to classify dementia and MCI proximate to death, as described previously. 14 Function in each of six domains (memory, orientation, judgment and problem solving, community affairs, home and hobbies, personal care) was rated on a 5‐point scale. An algorithm converted the six domain scores to an overall rating of no cognitive impairment (score = 0), MCI (score = 0.5), or dementia (score >0.5).…”
Section: Methodsmentioning
confidence: 99%
“…We used the informant portion of the Clinical Dementia Rating Scale 13 to classify dementia and MCI proximate to death, as described previously 14 . Function in each of six domains (memory, orientation, judgment and problem solving, community affairs, home and hobbies, personal care) was rated on a 5‐point scale.…”
Section: Methodsmentioning
confidence: 99%
“…Participation in cognitive activities was calculated based on reported time spent reading books, magazines, newspapers, and playing games; these four items were queried in both ROS and MAP 32,33 . Neuroticism was measured using 12 items from the Revised NEO Personality Inventory (NEO‐PI‐R), and scores could range from 0 to 48, with higher scores indicating more neuroticism 34 . Depressive symptoms were assessed using a modified, 10‐item version of the Center for Epidemiologic Studies Depression scale (CES‐D), with one point assigned for each reported depressive symptom 35 .…”
Section: Methodsmentioning
confidence: 99%
“…32,33 Neuroticism was measured using 12 items from the Revised NEO Personality Inventory (NEO-PI-R), and scores could range from 0 to 48, with higher scores indicating more neuroticism. 34 Depressive symptoms were assessed using a modified, 10-item version of the Center for Epidemiologic Studies Depression scale (CES-D), with one point assigned for each reported depressive symptom. 35 Further, we examined the APOE ε4 genotype; this is an important risk factor for Alzheimer's dementia and AD pathology, but not for CR, as a way to examine the function of our CR measures for null relations as well.…”
Section: Other Covariates At Cohort Baselinementioning
confidence: 99%
“…Because the index cases were decedents, the study was determined to be of non-human subjects in the United States and IRB exempt in the USA. As previously described [ 20 ], enrollment for PARDoS takes place in the State of Sao Paulo and prioritizes Black/Mixed decedents who are 65 years or older at death, and White decedents with fewer than 9 years of education enriched with admixed ancestry. Many decedents, however, were born in different States.…”
Section: Methodsmentioning
confidence: 99%